1973
DOI: 10.2307/1942159
|View full text |Cite
|
Sign up to set email alerts
|

Rock‐Face Populations of the Mountain Salamander, Desmognathus Ochrophaeus, In North Carolina

Abstract: The ecology and life history of Desmognathus ochrophaeus inhabiting wet rock faces at high elevations near Highlands, North Carolina, were studied. Comparisons were made with rock—face populations in Great Smoky Mountains National Park and with woodland populations at Rabun Bald, Scaly Mountain, and Blue Valley in the Blue Ridge Mountains. The reproductive cycle in rock—face populations is annual; spawning occurs mostly in July and August, and females begin to emerge from brooding as early as late August. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 31 publications
(54 reference statements)
1
21
0
Order By: Relevance
“…3 by individuals between 30and 34 mm SVL with ovarian follicles greater than 1.00 mm diameter. The size and age at maturity observed during this study are similar to rockface populations reported byTilley (1974), although three of the four rockface populations studied byHuheey and Brandon (1973) matured at somewhat smaller size.Maturing ovarian follicles appeared to reach a maximum size between 2.50 and 3.00 mm diameter(Figs. 1 and 3); only 2 individuals had ovarian follicles exceeding 3 mm Martof and Rose (1963).…”
supporting
confidence: 89%
“…3 by individuals between 30and 34 mm SVL with ovarian follicles greater than 1.00 mm diameter. The size and age at maturity observed during this study are similar to rockface populations reported byTilley (1974), although three of the four rockface populations studied byHuheey and Brandon (1973) matured at somewhat smaller size.Maturing ovarian follicles appeared to reach a maximum size between 2.50 and 3.00 mm diameter(Figs. 1 and 3); only 2 individuals had ovarian follicles exceeding 3 mm Martof and Rose (1963).…”
supporting
confidence: 89%
“…Sampling locations of litter bags and origins of terrestrial transects were spatially separated P10 m. Removal sampling did not commence until litter bag and transect sampling was complete. With the exception Eurycea wilderae, focal salamanders of this study are known to be relatively philopatric (home ranges < 8.5 m 2 ), and move only short distances between observations (Huheey and Brandon, 1973;Kleeberger, 1984;Camp and Lee, 1996;Peterman et al, 2008). As such, salamanders observed using each method can be considered independent observations with little to no double counting.…”
Section: Sampling Protocolmentioning
confidence: 92%
“…Because time varied with each sampling period and nocturnal activity of salamanders varies throughout the night (Hairston, 1949;Keen, 1984), an individual covariate of sample time was incorporated into removal models. Due to the discrete sampling period (6 days) and relative philopatry of salamanders (Huheey and Brandon, 1973;Kleeberger, 1984;Camp and Lee, 1996;Peterman et al, 2008), we are confident that births and deaths are a nonissue, while immigration and emigration can be considered negligible. In another removal experiment, Hairston (1986) found no evidence for immigration into removal plots by either Desmognathus monticola or Desmognathus ochrophaeus (now recognized as D. ocoee).…”
Section: Removal Samplingmentioning
confidence: 95%
“…Four of the 5 populations occur in wet rockface habitats, where seepage of the water table flows over road cuts or natural rock faces. These sites in the Southern Appalachians support dense populations of D. ocoee and other salamanders (Huheey & Brandon, 1973;Tilley, 1973Tilley, , 1980. All life stages including reproduction occur in the rockface habitats.…”
Section: Study Sitesmentioning
confidence: 73%